Local Potential-Based Sustainable Curriculum in Vocational Education: A Bibliometric Analysis - Lubis, Muhammad Ripqi; Widiaty, Isma; Sugiarti, Yatti (Journal of Vocational Education Studies, 2025)
The Sustainable Development Goals (SDGs) concept focuses on poverty eradication, gender equality, reducing child mortality, and environmental protection. Education plays a central role in achieving these goals, by providing quality and inclusive learning opportunities for all, including non-traditional groups and people with disabilities. In this context, quality vocational education aims to develop skills relevant to global issues, such as digitalization and renewable energy, and shape awareness of social change, the environment and sustainable development. Sustainable curricula, which integrate local potential, are an important part of supporting sustainable development. This study aims to analyze trends, roles, and research developments in vocational education related to local potential-based sustainable curriculum through a bibliometric approach. Data was collected using keywords related to sustainable curriculum and local potential, which resulted in 594 documents from 1972 to 2025. The study also identified publication trends and the most productive countries in local potential-based sustainable curriculum research, as well as dominant authors and keywords. Results show a significant increase in publications since 2004, although there was a decline in the period 2020-2022 due to the COVID-19 pandemic. The research also shows the importance of sustainable curriculum in facing global education challenges, with a focus on the relevance of education policy to social and global change